Pengaruh Pupuk NPK Majemuk terhadap N-Total, Serapan N, dan Hasil Umbi Bawang Merah (Allium ascalonicum L.) pada Inceptisols Asal Jatinangor - Shindy Widiana; Anni Yunarti; Emma Trinurani Sofyan; Dirga Sapta Sara (Soilrens, 2020)
Shallot (Allium ascalonicum L.) is a horticulture commodity that has a lot of benefits and also prospective due its increasing demand. Annual shallot productivity in Indonesia is unstable due to nutrient degradation on agricultural land, therefore efforts are needed to promote the productivity of shallot. One of the solution using NPK fertilization. This experiment aimed to determine the effect of NPK compound fertilizer on N total, N-uptake, and shallot bulb yield. This research conducted at the Soil Chemical and Plant Nutrition Experiments Field, Faculty of Agriculture, Padjadjaran University, Jatinangor, from February to June 2019. The experimental design used was Randomized Block Design (RBD) consisted of one control treatment, one N, P, K single fertilizer treatment (250 kg ha-1 Urea, 125 kg ha-1 ZA, 200 kg ha-1 SP-36, and 250 kg ha-1 KCl), and eight NPK compound fertilizer treatments in various doses with three replications. The results showed that the NPK compound treatment affected the total N, N uptake, and shallot bulbs yield. Treatment of 75% NPK compound (675 kg ha-1) gave the highest results of fresh bulbs weight at 41.64 g/clump and dry bulbs weight at 25.27 g/clump.